Patients’ Characteristics and Factors Influencing Success Rate of ESWL in Rumah Sakit Umum Daerah Kardinah, Tegal - Cipta, Wahid; Ali, Zulfikar (Indonesian Urological Association, 2017)
Objective: To evaluate which factors influencing success rate of extracorporeal shock wave lithotripsy (ESWL) in Kardinah Hospital Tegal. Material & methods: This was a retrospective study from secondary database of patients diagnosed with ureter or kidney stone whom underwent ESWL procedure in RSUD Kardinah Tegal from April 2012 to November 2015. Multivariate analysis and Chi-square analysis from SPSS ver. 19 were used to evaluate all the factors related to success rate of ESWL. Results: There were 314 patients included in this study with 59.5% of them were male patients. The average age of patients was 50 ± 5.5 years old. In 256 cases of kidney stones, there were 69 (26.9%) cases with size <10mm, 160 (62.5%) cases with a size of 10-20mm, and with a size >20mm by 27 (10.5%) cases. For ureteral stones, there were 46 (79.3%) cases with size <10mm, 11 (18.9%) cases with a size of 10-20mm, and 1 (1.7%) case with size >20mm. In general there were 238 (75.7%) of patients received no additional ESWL procedure while 61 (19.4%) patients underwent 2nd ESWL procedure, 33 (10.5%) patients underwent 3rd ESWL procedure, and 11 (3.5%) patients underwent more than 4 ESWL procedures. Kidney stones with a size <10mm, ureteral stones with size <10mm got, and location of the stone had p value of p=0.0015, p=0.001, and p=0.031 respectively. Other factors such as gender, age, stone opacity, and the number of shock given did not affect the success of ESWL. Type of lithotripter were not related to SFR in patient with kidney stone but was significantly related in ureter stone with p=0.078 and p=0.04 respectively. Conclusion: Most of patients reached stone free condition after the first ESWL procedure. Factors that influence the success of ESWL were the stone size and stone location. Kidney stone size <10mm and ureter stone <10mm had the highest SFR. Types of lithotripter were not related to SFRs in patients with kidney stone but were significantly related in ureteral stone with Medispec EM1000 electromagnetic and Huikang HK-V electromagnetic had the highest SFRs.